AUTOMATIC CREATION OF PRINT OUTPUT OF SERVICE ROUTES (Perner's Contacts, 2019)
The paper describes the process of creation itineraries as an endpoint of the process of optimization of service routes. There are described methods and software tools used for an automated creating high-quality print outputs.
Keywords: well-documented programs; markup language; Markdown; knitr; itinerary